Dynamical and steady state performance analysis of DC series motor and induction motor powered by an autonomous PV generator using MPPT. (15th August 2019) - Abuashour, Mohammed Ibrahim; Sweidan, Tha'er Omar
This paper presents the dynamical and steady state analysis of DC series motor and induction motor fed by photovoltaic generator at different solar irradiance levels. The maximum power point of current/voltage (I/V) characteristic of the PV generator is achieved for different solar intensities, by utilising an open voltage method. The nonlinear operational behaviour of (I/V) characteristics of the PV generator at various solar intensities and the magnetisation curve of the ferromagnetic material of the DC series motor are modelled by high order polynomial mathematical expressions. The dynamical and steady state analysis of the DC series motor and induction motor fed by PV generator at different solar intensity has been tested and investigated; also the dynamical and steady state analysis of DC series motor and induction motor is also farther investigated and studied as a step change in solar intensity levels with fixed loads torque for both motors. All numerical simulations are executed using MATLAB software.